Sentiment analysis : mining opinions, sentiments, and emotions - Liu, Bing, 1963- (Cambridge : Cambridge University Press, 2020)
Sentiment analysis is the computational study of people's opinions, sentiments, emotions, moods, and attitudes. This fascinating problem offers numerous research challenges, but promises insight useful to anyone interested in opinion analysis and social media analysis. This comprehensive introduction to the topic takes a natural-language-processing point of view to help readers understand the underlying structure of the problem and the language constructs commonly used to express opinions, sentiments, and emotions. The book covers core areas of sentiment analysis and also includes related topics such as debate analysis, intention mining, and fake-opinion detection. It will be a valuable resource for researchers and practitioners in natural language processing, computer science, management sciences, and the social sciences. In addition to traditional computational methods, this second edition includes recent deep learning methods to analyze and summarize sentiments and opinions, and also new material on emotion and mood analysis techniques, emotion-enhanced dialogues, and multimodal emotion analysis.
Title from publisher's bibliographic system (viewed on 21 Sep 2020).
Keywords: Natural language processing (Computer science); Computational linguistics; Public opinion -- Data processing; Data mining; Discourse analysis -- Data processing; Language and emotions